Empowering lecturers: How culture, training, and rewards drive performance with Islamic work ethics as the key - Zulpikar, Zulpikar; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2024)
This research aims to address the gap in understanding key factors influencing Lecturer Performance in Islamic-based higher education, particularly the roles of Organizational Citizenship Behavior (OCB), Employee Engagement, and Islamic Work Ethic (IWE). The study explores how Cultural Change and Training impact Lecturer Performance through OCB and Employee Engagement as mediators, with IWE moderating these relationships. Using survey methodology, data were collected from lecturers in Islamic-based institutions in Aceh through structured questionnaires measuring these variables. The analysis, conducted using Structural Equation Modeling (SEM) with AMOS, highlights the significant roles of OCB, Employee Engagement, and IWE in enhancing performance. The findings also reveal how Islamic values influence the interplay between management practices and performance outcomes. While the reliance on self-reported data and focus on specific variables may limit the study, it contributes valuable insights into the importance of strategic Cultural Change and Training initiatives in fostering a supportive organizational culture, aligning employee behavior with institutional goals, and advancing lecturer development and institutional success.